The mediating effect of BMI in serum vitamin D related sleep deprivation based on the NHANES database - Gong, Boya; Xu, Bei; Wang, Chaoban; Guo, Xia (Frontiers in Nutrition, 2025)
BackgroundSleep deprivation are a widespread condition globally, posing significant risks to individuals’ physical and mental health. Existing studies have explored the associations between sleep deprivation, vitamin D, and obesity. However, there is limited research on the combined effects of serum vitamin D and obesity. To address this gap, we conducted a cross-sectional study using the NHANES database to investigate the mediating role of BMI in serum vitamin D-related sleep deprivation among Americans.MethodsOur study included 20,865 participants from the NHANES database (2007–2018, 2021–2023). Logistic regression was utilized to assess the relationship between vitamin D levels and sleep deprivation. Mediation analysis was performed to examine the role of obesity in the association between vitamin D and sleep deprivation.ResultsIncreased vitamin D levels coupled with a BMI below the 75th percentile significantly reduced the risk of sleep deprivation to 0.70 times (95% CI: 0.64–0.77; p < 0.001) that of individuals with insufficient vitamin D and a BMI above the 75th percentile (>33.1 kg/m2). Serum vitamin D showed a direct significant effect on reducing sleep deprivation risk (β total = 1.92*10−3, P dir < 0.001), and its indirect effect through BMI was also highly significant (β indir = 7.59*10−5, P indir < 0.001). In the fully adjusted model, compared with the VD Inadequate and BMI > 75% group, the VD Sufficient and BMI < 75% group had a reduced risk of sleep deprivation (OR = 0.7, 95% CI = 0.64–0.77).ConclusionThis study demonstrates that in American adults, vitamin D can influence sleep deprivation both directly and indirectly through its impact on BMI. Therefore, for individuals suffering from sleep deprivation, vitamin D supplementation might offer potential benefits. Enhancing vitamin D levels could mitigate sleep deprivation risks, particularly when associated with lower BMI values.